2015
DOI: 10.1016/j.coi.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatially and temporally controlled immune cell interactions using microscale tools

Abstract: Many critical immunological responses are mediated by cell-cell interactions. Despite their capabilities, traditional techniques that rely on snapshot analysis or ensemble measurements can only provide a fragmentary picture of the complexity of these interactions. Emerging classes of new and versatile microscale tools hold great potential for enabling detailed investigation of these interactions with precise control in space and time, multiplexed measurement capability and high-throughput single-cell analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…8587 Moreover, microfluidic co-culture systems, including those based on valved microfluidics, 88 microfluidic cell trap arrays, 89 and droplet microfluidics, 9091 have the ability to control cell-cell interactions at a single-cell resolution in a high-throughput manner by generating and manipulating cell pairs with hydrodynamic forces and/or other physical forces. 9293 Such high-throughput, single-cell-level co-culture systems can simplify the complexity of cell-cell interactions and provide a wealth of information related to cell heterogeneity.…”
Section: The Cell Microenvironmentmentioning
confidence: 99%
“…8587 Moreover, microfluidic co-culture systems, including those based on valved microfluidics, 88 microfluidic cell trap arrays, 89 and droplet microfluidics, 9091 have the ability to control cell-cell interactions at a single-cell resolution in a high-throughput manner by generating and manipulating cell pairs with hydrodynamic forces and/or other physical forces. 9293 Such high-throughput, single-cell-level co-culture systems can simplify the complexity of cell-cell interactions and provide a wealth of information related to cell heterogeneity.…”
Section: The Cell Microenvironmentmentioning
confidence: 99%
“…Nanolitre micro-well arrays enable the study of single-cell phenotyping of rare cells, such as antigen-specific T cells and B cells. Studies on these rare subsets have revealed structure-function relationships between molecular synapses and signalling cascades [ 70 ]. Co-culture studies together with barcoded antibody arrays enabled the examination of the influence of paracrine signalling molecules on tumour cell function and signalling networks via the multiplexed detection of both intracellular and secreted proteins/cytokines [ 71 , 72 ].…”
Section: Enhanced Flow Cytometry Techniques For Single-cell Analysmentioning
confidence: 99%
“…Cell-cell interactions are ubiquitous in organisms and can potentiate disease, but methods to selectively visualize and ultimately control them are lacking. [1][2][3] Current strategies rely on imaging with fluorescent proteins [4][5][6][7][8] or enzymatic labeling. [9][10][11][12] While useful, many of these methods are not generalizable to multiple cell types or provide only short-lived signals.…”
Section: Introductionmentioning
confidence: 99%